A retrospective study of equalization funding in California community colleges and its association with student success and student course retention - Hollabaugh, Kristin M., author; Davies, Timothy Gray, advisor; Most, David, advisor (Colorado State University. Libraries, 2009)
The Serrano v. Priest decision is very important in California. In 1971, it was decided by California State Supreme Court in 1971 that California school financing system was unconstitutional under the equal protection provision of the State constitution. As California public education financing has long had disparate funding levels, the purpose of this quantitative study was to examine the association between equalization funding and student course success and student course retention in California Community Colleges. Archival student success and student course retention data was used for 107 California Community Colleges, and the years reviewed were: Year 1 (2002-03); Year 2 (2003-04); Year 3 (2004-05); Year 4 (2005-2006); Year 5 (2006-07); Year 6 (2007-08). First year of equalization funding was 2004-2005, or Year 3 of the study. Only the Fall and Spring terms were analyzed for each of the years. No summer or intercessions were included in the data calculations. In addition, for the purposes of this study, a college was treated as a funded college if it was eligible for funding for the first year of the equalization program (2004-2005). Conversely, a college was treated as a non-funded college if it was not eligible for additional funding for the first year of the equalization program. The time-over-change study produced several findings. First, when only looking at two subgroups (funded and non-funded) there was an association between equalization funding and student course success. In other words, the mean success lines became markedly closer together at the end of the study than at they were at the beginning of the study. Second, when those subgroups were then broken down by multi-campus college districts and single-campus college districts, again there appeared to be association between student success and infusion of equalization funding. What became apparent, however, was the uniquely-shaped lines of colleges in the Los Angeles Community College District, so a decision was made to pull those ten colleges out of the mix. In addition, Basic Aid District Colleges were pulled out of the subgroups. When Los Angeles colleges and Basic Aid District Colleges were pulled out of the mix, there was not a meaningful association between course success and equalization funding. In addition, in all cases, there was no meaningful difference for course retention-on any level.
Keywords: California; community colleges; course retention; equalization funding; success; community college education; education finance; educational leadership; college students